Pengaruh Digital Payment Dan Digital Marketing Terhadap Keputusan Berwirausaha Dan Keberlanjutan Usaha Di Era Ekonomi Digital - Mendrofa, Pewarni; Larosa, Yoel (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The development of financial technology and digital marketing has fundamentally changed the business landscape. This study aims to analyze the influence of digital payment usage and digital marketing strategies on individual interest in entrepreneurial decisions and their impact on business sustainability. Using descriptive qualitative methods with secondary data analysis from the 2021-2026 digital economy development report, this study found that the ease of digital transactions lowers barriers to entry for new entrepreneurs. Meanwhile, digital marketing plays a crucial role in expanding market reach, ensuring sustainable cash flow. The results show that the integration of these two variables creates a more resilient business ecosystem in developing regions.